Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Transportasi Jakarta - Silfia Fitri Anggraeni; Purwatiningsih, Purwatiningsih; Ratih Setyo Rini (Global Leadership Organizational Research in Management, 2024)
Human resource stewardship is a series of activities and strategies that aim to maintain and improve the well-being, motivation, engagement, and productivity of employees in an organization. Employee performance is an important indicator of their contribution to organizational success because good performance can create a positive work environment and strengthen individual motivation to perform even better. Work environment and work motivation are two factors that can affect employee performance. PT Transportasi Jakarta is a company that operates public transportation services in Jakarta. PT Transportasi Jakarta employees pursue their careers in a unique work environment, driven by a family-based organizational culture and discipline, so that they can achieve operational targets and provide the best service to the community. The purpose of this study was to determine the effect of work environment and work motivation on employee performance simultaneously or together. The method used in this study uses statistical quantitative methods and uses sample calculations with the Yamane formula which results in 98 respondents. The data collection technique in this study used a questionnaire. The results of this study indicate that the work environment and work motivation have a positive and significant influence on employee performance as seen in the simultaneous f test, namely the fcount value of 91.492 > ftabel 3.09.